TINGKAT PERTUMBUHAN DAN KARAGINAN RUMPUT LAUT EUCHEUMA COTTONII DI PERAIRAN BATUBAO TELUK KUPANG DENGAN MENGGUNAKAN BIBIT PETIKAN (F2) - L. M. Takanjanji; Marcelien Dj. Ratoe Oedjoe; Yulianus Linggi (Jurnal Akuatik, 2018)
Abstract - The study has been conducted in Batubao,west region of Kupang, for 3 mounths, to know the rates of E. cottonii growing and carragenan content by second pitch of seaweed reding. The second pitch seeds were the newtreatent that thalus was pitched out from two times 25 days cultivation of F2_seed. The rates of growing and carragenan production of F2_seed was companing to 45 days cultivation of sea weed, a conventional seed called control seed. Both of seed eas cultivated subseguently for 45 days. The results shows that the biomas of F2_seed treatment raise to 636±23,30 g and control are 617±23,97 g. The carragenan protection of F2_seed are 7,2% and control are 6,4%. The corelysion is growing and carragenan production of F2_seed treatment are higher them the conventional seed. Keyword : Seaweed, Eucheuma cottonii, Growth, Carrageenan.